PENINGKATAN KOMPETENSI GURU DALAM PENERAPAN GAMIFIED LANGUAGE LEARNING UNTUK ENGLISH FOR YOUNG LEARNERS DI KINDERCYL - Puspita, Hilda; Sasmita, Ruwaiza; Marpaung, Tiara Azzahra (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2025)
This community service program is intended to enhance preschool teachers' skills in using gamified language learning for teaching English to young learners at Kindercyl Learning Space. The program was created to encourage teachers who had limited experience using digital tools in their language class. The program included training, hands-on practice, simulated lessons, and mentoring, all using digital tools like Quizizz, Kahoot, and Canva. The results showed that teachers improved a lot in making interactive teaching resources and using student-centered, engaging methods in class. They became more creative, worked better together, and were better at using technology to provide meaningful learning experiences. Also, the program encouraged stronger teamwork between teachers, students, and partner schools, connecting classroom practice with academic theory. Keywords: preschool teachers, language learning, gamification, digital teaching media, young learners